Determining Sales Patterns of Beauty Products Using the Apriori Algorithm in Data Mining - Windi Maharani; Raissa Amanda Putri (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
The use of data mining technology is a must to extract information that can help in making better decisions, especially in the beauty product industry, where competition is getting tougher. Changes in lifestyle and an increase in people's income lead to an increase in public consumption of beauty products. From these problems, a data mining system was created to determine the sales pattern of beauty products using the Apriori algorithm method. The goal is to get information about products that are often purchased by consumers so that they can prepare their needs with business strategies. The use of Apriori can perform the process of extracting information from the database to find association rules between a set of data or a combination of items/itemsets. The results of this study formed an application that was built using the Python programming language to analyze product sales at Underprice Skincare stores using the apriori algorithm. The data generated from the application process of data mining will be used as a reference for stores to prepare stock availability and can design the right business strategy to increase sales of beauty products at Underprice Skincare stores.